2018
DOI: 10.7717/peerj.4961
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioral responses of house sparrows to repeated stressors

Abstract: Despite decades of research, we still lack a complete understanding of what factors influence the transition of the necessary and adaptive acute stress response to what has become known as chronic stress. This gap in knowledge has illuminated the necessity for studies that examine the thresholds between these two sides of the stress response. Here, we determine how repeated exposure to acute stressors influences physiological and behavioral responses. In this repeated measures study, house sparrows (Passer dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 72 publications
5
16
3
Order By: Relevance
“…This result for baseline Cort was not surprising. A closely related study that exposed birds to two different stimuli to initiate chronic stress also did not significantly alter baseline Cort in the initial 4 days (Gormally et al, ). This lack of change highlights that baseline Cort does not always change in a consistent manner in different species.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This result for baseline Cort was not surprising. A closely related study that exposed birds to two different stimuli to initiate chronic stress also did not significantly alter baseline Cort in the initial 4 days (Gormally et al, ). This lack of change highlights that baseline Cort does not always change in a consistent manner in different species.…”
Section: Discussionmentioning
confidence: 89%
“…The experimental design was based on prior chronic stress studies that indicated that the hormonal effects of chronic stress are typically initiated within 8–12 days (Awerman & Romero, ; Cyr et al, ; DuRant, Arciniega, Bauer, & Romero, ; Gormally, Wright‐Lichter, Reed, & Romero, ; Lattin & Romero, ). In several of these studies, birds were exposed to different stressors at four different unpredictable times throughout the day for up to 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uric acid was measured using Amplex® Red Uric Acid/Uricase Assay Kits (Molecular Probes; Gormally, Estrada et al, 2019; Gormally, Wright‐Lichter, Reed, & Romero, 2018). Two‐hundred microliters of reaction buffer were used to dilute samples (2–3 μl plasma) and horseradish peroxidase and Amplex Red Reagent were added to convert uric acid to a red fluorescent product.…”
Section: Methodsmentioning
confidence: 99%
“…Millet, Bennett, Lee, Hau, & Klasing, 2007), suggesting a response latency of about 1 hr (Figure 1). Bacterial killing capacity also can be affected by longer term stimuli, including habitat quality (Hopkins & DuRant, 2011), seasonal variation (Zimmerman, Paitz, Vogel, & Bowden, 2010), captivity (Love, Lovern, & DuRant, 2017) and repeated stressors (Gormally, Wright‐Lichter, Reed, & Romero, 2018; Table S1). Consequently, bacterial killing capacity can reflect stressor durations on the order of at least months, possibly even lifetime (Figure 1).…”
Section: Immunementioning
confidence: 99%